Desain Instruksional Materi Luas Permukaan Bangun Ruang Untuk Sekolah Dasar dalam Pembelajaran Jarak Jauh - Gesti Marsaulina Pakpahan; Tian Abdul Aziz (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This paper presents an analysis of instructional development for space geometry lessons intended for educational institutions in elementary schools, especially grade 6 in Indonesia. The selected lesson covers the topic of the surface area of a triangular prism. Learning development is carried out by conducting a needs and learner analysis as well as a specific task analysis for the selected lesson. Performance objectives and learning outcomes are discussed in detail and their alignment with each other and the overall instructional objectives.